消費者特質與銀行債信評等之探討;A Study of Consumer Personality Trait and bank’s loan credit - 楊喜榮 (2012)
2005年，美國因貸款違約事件不斷增加，爆發近年以來規模最嚴重的房地產泡沫化，危及金融相關產業的情況就越演越烈，歷經了雷曼兄弟破產，美林證卷的收購事件，而曾有全球最富足國家之稱的冰島，也遭受波及，目前金融海嘯已席捲到歐洲。全球經濟嚴重衰退，也代表著與國際金融市場緊密連結的台灣，也應在貸款違約上得有所警惕。 本研究擬就T銀行的六種消費者貸款類型之貸款用戶，分為成功與失敗兩個群組，分析外顯與內隱九型人格特質因子，與銀行授信成效研究兩方因素之關聯性，共發送300份問卷，有效問卷共計279份。研究發現經由羅吉斯迴歸分析所建構的模型，九種人格中的第二型(助人型)、第四型(浪漫型)、第七型(享樂型)與第八型(領導型)的消費者，對影響申貸失敗的強度最大；而第三型(實踐型)、第五型(思考型)與第九型(和事佬型)的消費者，其影響申貸成功的強度最大。有別於公有銀行審核的角度，試圖找出不同的消費者人格族群，可有助於降低貸款成為呆帳的風險，審慎建立一套良好的信用評估準則，以供授信人員遵循。另彙整出成功申貸消費者行為重要程度最高的關鍵因素共九點，提供策略規劃人員做參考。 Back into 2005, the USA suffered from the most serious housing bubble because of the increasing events that people could not pay their housing loans, and this situation jeopardizing its finance-related industries seemed to be worse and worse. Experienced the Bankruptcy of Lehman Brothers (2008) and mergence of Merrill Lynch by Bank of America (2009), even though the Iceland use to be so-called the most prosperous country among the worlds could not sit on the sidelines. The financial Tsunami has been sweeping the Europeans, and global economics is still under the severe recession. This means Taiwan with its financial market linking to international markets closely shall have to be vigilant on the contract break of loans. This study takes the six consumer loans types of users in T bank, and divides the six types into groups successful or failed cases, and then analyzes the relation between the explicit and implicit Enneagram of personality and the credit extensions effect of the bank. The samples using for the research are collected from 279 valid questionnaires by sending out the total number of 300 ones. The research finds that the 2nd(Helper), 4th(Individualist), 7th(Enthusiast), and 8th(Challenger) types of consumers have most significant influences upon the fail loan cases, and on the other hand, the 3rd(Achiever), 5th(Investigator), and 9th(Peacemaker) types contribute the most to the successful loan cases based on the logistic regression model. Different from the verified aspect of public banks, the attempt to discovery different groups of consumers’ personality and then build a set of good verified rules for those in charge of credit extended verification to follow will help to bring down the risk of loan turning into bad debt, and then build. The study also extracts 9 consumer behavior factors with the most important degree to the successful loan cases for the strategy-planning people to refer to.